Объяснение:
y=4x−(7/2)x²−(2/3)x³
y'=(4x−(7/2)x²−(2/3)x³)'=4-(7*2/2)х²⁻¹-(2*3/3)х²=4-7х-2х²
y''=(4-7х-2х²)'=-7-4х
4-7х-2х²=0
х₁ ₂ = (7±√(49-4*(-2)*4))/-4
х₁ ₂ = (7±√81)/-4
х₁ ₂ = (7±9)/-4
х₁ = (7-9)/-4 х ₂ = (7+9)/-4
х₁ = -2/-4 =1/2 х ₂ = 16/-4=4
y(х)''=-7-4х y(х)''=-7-4х
y(1/2)''=-7-4*1/2 y₂(-4)''=-7-4*(-4)
y(1/2)''=-7-5=-12 y₂(-4)''=-7+16=9
y₁ (1/2)''∠0 максимум 0 ∠ y₂(-4)'' минимум.
y₁ =4*0,5−(7/2)*0,25−(2/3)*0,125 y₂=4*(-4)−(7/2)*16−(2/3)*(-64 )
y₁ =1 целая и 1/24 y₂=-29 целых и 1/3
(0,5 ; 1 1/24) - максимум (-4; 29 1/3) - минимум
Поделитесь своими знаниями, ответьте на вопрос:
Построить график функции y=x3-3x2+4
4х-5,5=5х-6х+4,5
4х-5,5=-х+4,5
4х+х=5,5+4,5
5х=10
х=2
г)7*(-3+2х)=-6х-1
-21+14х=-6х-1
6х+14х=21-1
20х=20
х=1
ж)4*(2-3х)=-7х+10
8-12х=-7х+10
7х-12х=-8+10
-5х=2
х=-0,4
б)4-5(3х+2,5)=3х+9,5
-3х-2,5=3х+9,5
-3х-3х=2,5+9,5
-6х=12
х=-2
д)2*(7+9к)=-6к+2
14+18к=-6к+2
6к+18к=-14+2
24к=-12
к=-0,5
з)-4*(-к+7)=к+17
4к+-28=к+17
4к-к=28+17
3к=45
к=15
в)0,4(6х-7)=0,5(3х+7)
2,4х-2,8=1,5х+3,5
2,4х-1,5х=2,8+3,5
3,9х=6,2
х=1,589...
е)6*(5-3с)=-8с-7
30-18с=-8с-7
8с-18с=-30-7
-10с=-37
с=-3,7
и)-5*(3а+1)-11=-16
-15а-5-11=-16
-15а=5+11-16
-15а=0
а=0
Надеюсь